Skills, knowledge, and attitudes important for present-day auditors - Siriwardane, Harshini P. (2014)
Recent accounting scandals have challenged and transformed the present-day role of auditors, making it timely and important to re-examine the skills, knowledge, and attitudes (SKAs) required of auditors in today's business environment. While prior studies have examined SKAs of accountants and internal auditors, and personal attributes of auditors, there is little research on auditors' SKAs. We propose and examine 20 SKAs important to present-day auditors. We survey experienced auditors in Singapore about the importance of these SKAs. Our participants rate professional integrity, assessing audit evidence, and having a questioning mind (indicative of professionalism competency) as the three most important SKAs. The participants also assess entry-level auditors' (ELAs) performance for each SKA. The difference between their importance and performance ratings is largest for business competency, particularly for knowledge of client's business. Our findings have implications for various accounting constituencies in terms of developing auditors' competencies.